A Model for home-based remote monitoring of asthmatic patients - Oduor, Julius Thomas (Strathmore University, 2017)
Asthma affects a large number of people in the world and it is the most common chronic illness of the lung among children. Monitoring and assessing the severity of a child’s asthma at home has proven difficult and costly in many low resource settings, like Kenya. This is due to lack of easy to use and cost effective in-home monitoring tools for children suffering from asthma. In this work, we present a wearable device that allows in-home remote monitoring of asthmatic child and instant determination of degree of asthma severity. Once the severity is known, the cases which are severe can be recalled to the clinic by the doctor for proper care and management. The device captures simultaneous measurements of heart rate and oxygen saturation using a pulse oximeter sensor. These readings are then analyzed using clinical algorithm for asthma management, and the resulting severity level sent to both the parent of the child and the assigned clinician. The device was developed using Arduino Uno microcontroller, pulse oximeter sensor and Global System for Mobile Communication (GSM) module.
Thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Information Technology (MSIT) at Strathmore University
Keywords: Asthma; Arduino Uno microcontroller; Internet of Things; pulse Oximeter Sensor